2020
DOI: 10.1021/acscatal.0c04133
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the RWGS Reaction via EPOC and In Situ Electro-oxidation of Cobalt Nanoparticles

Abstract: The electrochemical promotion of catalytic activity by non-noble transition metals is rarely reported in the literature. Here, Co nanoparticles were utilized for the electrochemical activation of CO2 hydrogenation under atmospheric pressure conditions. A range of transient kinetic experiments in conjunction with X-ray photoelectron spectroscopy and imaging techniques were employed to correlate the observed catalytic activity with the electronic and morphological characteristics of the cobalt catalyst surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 60 publications
2
38
1
Order By: Relevance
“…53 The catalyst was activated above 300 °C and the catalytic rate increased with temperature in all cases. Under the same conditions, the open-circuit CO rate showed to be two times higher than those of recently reported FeO x and CoO x NPs on YSZ 25,26 but was still lower than that of ruthenium, a noble metal catalyst. 21…”
Section: Resultscontrasting
confidence: 45%
See 2 more Smart Citations
“…53 The catalyst was activated above 300 °C and the catalytic rate increased with temperature in all cases. Under the same conditions, the open-circuit CO rate showed to be two times higher than those of recently reported FeO x and CoO x NPs on YSZ 25,26 but was still lower than that of ruthenium, a noble metal catalyst. 21…”
Section: Resultscontrasting
confidence: 45%
“…Panaritis et al 25 illustrated that the oxidation state of FeO x /YSZ could be controlled by the application of a small current or potential and thereby influenced the RWGS reaction rate. Similarly, Zagoraios et al 26 showed an EPOC effect for RWGS reaction by using CoO x /YSZ, which also possessed multiple oxidation states. Both Fe and Co showed comparable enhancement performance to noble metals, but the steady-state reaction rates under open-circuit potential were still inferior and the promotion phenomenon was not stable, accompanied by rapid changes in the beginning and end of polarizations.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A promising method to obtain high RWGS activity is through the use of the electrochemical promotion of catalysis (EPOC) effect and the in situ electro-oxidation of non-noble transition metals. 21 More specifically, the EPOC effect, also known as non-faradaic electrochemical modification of catalytic activity (NEMCA) is a highly utilized tool in heterogeneous catalysis over the past 40 years. [22][23][24][25][26][27] This effect is commonly studied with a simple and straightforward experimental set up involving three metal electrodes deposited onto a solid electrolyte/ion conductor as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, Co x Fe 1‐ x O y has been prepared through simple ball milling (BM method), a facile mechanochemical redox method, and a series of catalysts with high surface area (131 m 2 g −1 ) was obtained, much higher than those of samples prepared via SG method (33 m 2 g −1 ) and CP method (49 m 2 g −1 ). The obtained‐catalysts were applied in the reverse water‐gas shift (RWGS) reaction, one of the most effective, essential, economical, and sustainable ways to utilize CO 2 waste by CO 2 hydrogenation 34,35 . The conversion rate of the hydrogenation catalyzed by Co x Fe 1‐ x O y in BM method was about 43% at 500 ℃, and the rates only reached 13.8% and 15.7% for the catalysts fabricated by SG method and CP method respectively under the same condition, indicating the mechanochemical redox process provides scope to extraordinary characteristics of the catalysts.…”
Section: Introductionmentioning
confidence: 99%